A new design of a microstrip rectenna at 5.8 GHz for wireless power transmission applications - Taybi Abdellah; Abdelali Tajmouati; Jamal Zbitou; Ahmed Errkik; Mohamed Latrach (Institute of Advanced Engineering and Science, 2019)
Due to the ever-increasing power demand, the need of electricity and eco-friendly power in every nook and corner of the world, many reaserch topics have been devoted to deal with this problematic. This paper is taking part of the proposed solutions with the presentation of a novel 5.8 GHz rectenna system for wireless power transmission applications. In one hand, a miniaturized 5.8 GHz circular polarized patch antenna has been designed and simulated by using the Advanced Design System (ADS). In the other hand, a rectifier structure has been investigated and optimized by the use of the Harmonic Balance method available in ADS. The circuit is based on 5 HSMS2820 Schottky diodes implemented in a voltage multiplier topology and a load resistance of 1 KOhm. Both of the structures have been validated by simulation and experimental results and good agreement has been concluded.